A general [18F]AlF radiochemistry procedure on two automated synthesis platforms. Issue 1 (25th January 2017) - Allott, L.; Da Pieve, C.; Turton, D. R.; Smith, G.
Abstract : The first general [ 18 F]AIF automated radiolabelling procedure developed on the GE Tracerlab FX FN (Left) and Trasis AllInOne (Right) platforms. Abstract : The aluminium fluoride-18 ([ 18 F]AlF) radiolabelling procedure has generated great interest because it is a simple, one-pot method that can be used to directly radiolabel small molecules, peptides and proteins without the requirement for a [ 18 F]fluoride drying step. Reported here is the development of an automated [ 18 F]AlF radiolabelling procedure of three different precursors (one small molecule and two peptides) on two automated synthesis platforms: GE TRACERlab FXFN and Trasis AllInOne (AIO). Aiming at the clinical translatability of a [ 18 F]AlF radiosynthetic methodology, the use of both platforms yielded radioconjugates with >98% radiochemical purity (RCP) within 26–35 min and required a single rapid purification step. The Trasis AIO platform gave improved [ 18 F]fluoride incorporation, and generally produced radioconjugates with a higher radiochemical yield (RCY) and effective specific activities (SA) when compared to the GE TRACERlab FXFN system.